Deciphering Synsepalum dulcificum as an Arising Phytotherapy Agent: Background, Phytochemical and Pharmacological Properties with Associated Molecular Mechanisms - Ee, Jia Wer; Appalaraju, Velaga; Rhanye, Mac Guad; Vetriselvan, Subramaniyan; Fuloria, Neeraj Kumar; Fuloria, Shivkanya; Choy, Ker Woon; Wu, Yuan Seng * (Universiti Kebangsaan Malaysia, 2022)
Medicinal plants with less side effects are paramount important for humankind to cure various ailments as compared to newly developed allopathic medicines. Synsepalum dulcificum Daniell (Sapotaceae), is well known as miracle fruits due to its distinctive taste-modifying property. This review aimed to discuss its recent reported pharmacological properties and associated molecular mechanisms as a novel phytotherapy agent. In addition, background, phytochemical analysis and toxicological studies were also discussed as the foundation and added values for this review. It was discovered that S. dulcificum is endowed with various classes of phytochemicals, such as flavonoids, tannins, alkaloids and saponins. This review ravelled that S. dulcificum is a potent medicinal plant associated with antioxidant, antidiabetic, antimicrobial, anticancer, anti-hyperuricemic, hepatoprotective, anti-hyperlipidaemic, and anticonvulsant activities, with less toxicity shown. Future research may explore further the corresponding phytochemicals, associated molecular mechanisms, toxicological and pharmacokinetic profile before subjecting to clinical testing.